ANALISIS PENGARUH KUALITAS LAYANAN, CITRA DAN PROMOSI TERHADAP TINGKAT KEPUASAN PENGUNJUNG PADA HIDDEN CANYON BEJI GUWANG - Ni Nyoman Novarini; Ni Putu Nita Anggraini (Forum Manajemen, 2017)
This study to puposses the effect of service quality, tourism image and tourism promotion to satisfaction Hidden Canyon Beji Guwang’ visitor. The type of research used is eksplanatory research with sample technique using purposive sampling and accidental sampling. Data collection techniques used were questionnaires distributed to visitors of Hidden Canyon Beji Guwang. The analysis technique used is multiple linear regression. From the analysis, it is known that the quality of service does not affect the satisfaction, the image of tourism has a positive effect on the satisfaction and promotion of tourism has a positive effect on visitor satisfaction.